How to Improve the Economic Policy Framework for the Housing Market in Israel - Hemmings, Philip (OECD Publishing, 2011)
Israeli house prices have risen by over 50% over the past three years. In part this reflects the fact that for several years housing construction had not kept pace with increases in the number of households. In response to these developments, hitherto sluggish planning-approval processes are being speeded up. However, in addition low interest rates have been boosting demand, and there are concerns that prices have already been driven to bubble levels. Efforts have been made to subdue demand, and the market has cooled off somewhat, but there remains a risk of a hard landing with a sharp downward price correction and a contraction in construction activity. Recent price developments are not the only economic issue in Israeli housing. As in a number of other OECD countries, housing policies favour home ownership through tax settings and subsidies for house purchase, potentially raising issues of labour mobility. More generally, housing support (public housing and rent support as well as subsidies for purchase) endeavours to fulfil an unusually wide policy agenda that goes beyond simply assisting low-income households with their housing needs. This Working Paper relates to the OECD 2011 Economic Survey of Israel (www.oecd.org/eco/surveys/Israel)
Keywords: Urban, Rural and Regional Development; Economics; Israel